Need Assessment of Relaxation Techniques based on Local wisdom for Children with Eruption Traumatism - Hidayah, Nur; Rusmana, Nandang; Asrowi, Asrowi; Apriani, Rizka; Hanafi, Husni; Saputra, Nur Mega Aris (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
This study aimed to identify the need for appropriate counseling services for children who have experienced eruption trauma. This research method uses a cross-sectional survey research design of elementary school teachers and parents of affected children on the slopes of Mount Semeru. Data were collected using structured interviews, questionnaires, and observation of field conditions. The analysis data used are descriptive-interpretative. The study's results identified (1) the need for post-traumatic counseling services based on local wisdom for children affected by the Semeru eruption and (2) aspects of local wisdom that became the content of post-traumatic counseling for children affected by the Semeru eruption. This research becomes the basis and recommendation to develop a post-traumatic counseling model based on the local wisdom of the Mount Semeru community that is theoretically and practically acceptable.